Lokakarya Satuan Pendidikan Aman Bencana (SPAB) dan Psychological First Aid (PFA) - Dinda Dwarawati; Eni N. Nugrahawati; Anna Rozana; Ayu Tuty Utami; Yasyfa Camilla Pudjiadi; Hasybi M. Azka; Hasmi Havila; M. Husni (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
One of the FPRB volunteers' tasks is to strengthen the capacity of schools in Kabupaten Bandung for the government-initiated program, namely socializing the SPAB (Satuan Pendidikan Aman Bencana). Given that a disaster situation is one that puts survivors in a state of crisis, the survivors (disaster victims) are likely to have emotional reactions in various ways. The FPRB Volunteers of Kabupaten Bandung are the PKM's special target for the 2020-2022 period. The reason for the FPRB Volunteers of Kabupaten Bandung being the subject of the PKM is due to the needs of the organization, which will soon be implemented in 41 schools in 31 sub-districts throughout Kabupaten Bandung as the beneficiaries of the SPAB carried out by the FPRB Volunteers of Kabupaten Bandung as participants. The research method used in the PKM is the experimental research method. The researcher conducted quantitative research using a pre-experimental design, type 1 group, pre-test-post-test (pre-test, single-group final test), called quasi-experimental. The result of the service is that the workshop that has been given has led to an increase in SPAB and PFA facilitation skills among FPRB volunteers.